The Complexity Of School-Based Management In Improving Teacher Quality - Sahabudin; Mahsur (International Journal of Sociology of Religion, 2024)
This research discusses the complexity of school-based management as a strategy to improve teacher quality. In the ever-evolving era of education, the role of school-based management becomes crucial in creating an effective learning environment. The concept of complexity is applied to describe the dynamics, interactions and challenges involved in managing teachers together in an educational environment. This study uses a qualitative approach with a focus on the implementation of school-based management and its impact on co-teachers at SD Negeri 3 Tirtanadi. Data were collected through interviews, observation and document analysis related to education policy. The research findings show that the complexity of school-based management includes factors such as leadership, stakeholder engagement, professional development and organisational culture. The results provide deep insights into how schools can effectively manage these complexities to improve teacher quality. The practical implications of this research involve crafting education policies that support the implementation of school-based management, empowering school leadership and strengthening collaboration among stakeholders. As such, this research makes a significant contribution to the understanding of the complexities of school-based management as a strategic endeavour in improving teacher quality in the contemporary education era.